Exploring risk perception and intention to improve the air quality - Sahrir, Syazwani; Yalçınkaya, Nermin Merve; Say, Nuriye (Malaysian Institute of Planners, 2022)
Numerous environmental issues, particularly those with higher risks, have steadily come to the forefront of the public's concerns in recent years with the increased awareness on environmental quality. For example, air pollution is one of the main causes of death worldwide and contributes to the rise in the risk of chronic diseases. In the Turkish city of Adana, air pollution has long been recognised as a serious environmental and health concern with well-documented negative consequences on human wellbeing. Although important, little is known about how the general public views the risk of air pollution. Thus, this paper focuses on risk perception and behavioural intention to air pollution. Adana city in southern Turkey was chosen as the study area. The results showed that sociodemographic factors and perceived risk of familiarity with air pollution are significant factors influencing Adana inhabitants' willingness to pay for bettering the air quality. Additionally, it implies that the authority might provide a significant contribution by creating strategies to lessen the effects of air pollution on people, particularly in cities where air pollution is a problem.